To find the coefficient of the second term in the expansion of \((a + 3)^7\), we can use the Binomial Theorem, which states:
\[ (a + b)^n = \sum_{k=0}^{n} \binom{n}{k} a^{n-k} b^{k} \]
In this case, \(a = a\), \(b = 3\), and \(n = 7\). The general term in the expansion can be given as:
\[ \binom{n}{k} a^{n-k} b^{k} \]
The second term corresponds to \(k = 1\) (since \(k\) starts from 0). Thus, we will calculate the term when \(k = 1\):
- Compute the binomial coefficient \(\binom{7}{1}\):
\[ \binom{7}{1} = 7 \]
-
Evaluate \(a^{7-1} = a^{6}\).
-
Evaluate \(b^1 = 3^1 = 3\).
Putting this together, the second term in the expansion is:
\[ \binom{7}{1} a^{6} (3^1) = 7 \cdot a^6 \cdot 3 = 21a^6 \]
Thus, the coefficient of the second term in the expanded form of \((a + 3)^7\) is:
\[ \boxed{21} \]